The Response of Private Consumption to Different Public Spending Categories: VAR Evidence from UK - Luigi Marattin; Simone Salotti (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2009)
This paper performs a Structural VAR analysis on UK economy using quarterly non-interpolated data from 1981 to 2005 in the attempt to verify and quantify private consumption's response to different components of public expenditure (government consumption, social spending and wage component). Our findings suggest that any empirical support of competing theoretical models on the issue would probably benefit from a disaggregation of government expenditure, rather than focusing on the aggregate measure. In fact, while shocks to pure government consumption trigger a RBC-like reduction in private consumption, shocks to the non-systematic component of social spending generate positive reaction, in line with the "credit-constrained-agents" approach. The cumulative impact on GDP after three years of a government spending shock (close to a negative 1% of GDP) is twice as much the social spending shock, with opposite sign. Government wage shocks do not seem to have any significant effects on private consumption. Public expenditure composition, rather than level, seems to be actually playing the most crucial role when it comes to aggregate demand support via effects on private consumption.
Keywords: 330